Four new species of Litoblatta from Argentina with a key to species based on males (Blattaria: Ectobiidae: Blattellinae) - Valverde, Alejandra Del Carmen; Crespo, Francisco A. (Zootaxa, 2021)
New diagnostic characters were used to study the genus Litoblatta Hebard: paraprocts, styles due to their shape and distribution of spines, and sclerites of the genitalia of the male with emphasis on the right complex. Male and female genitalia are described in detail. Four new species of cockroaches are described, Litoblatta elisae, Litoblatta lutea, Litoblatta misionerae, and Litoblatta tucumanae. The number of species recorded for Argentina rises to 7 and a key for male determination is provided. The geographic distribution of the studied species of cockroaches is extended.